Surgery patients’ perception about anesthesia and role of anesthesiologist - Piya, Roshan; Shrestha, Anil; Pradhan, Manisha; Amatya, Shirish Prasad; Shrestha, Aimi; Poudel, Sangeeta (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Anesthesiologists play an important role in the management of peri-operative risk and the perception of patients towards anesthesia and the role of anesthesiologists are often underestimated. Newer initiatives are required to increase communication with patients and educate them about the importance of anesthesia during surgery. The study aims to assess perception in relation to education level and patients’ previous exposure to anesthesia about anesthesia and the role of the anesthesiologist.Method: A cross-sectional, predesigned Nepali questionnaire-based study was conducted after approval from the Institutional Review Committee (IRC), Patan Academy of Health Sciences. A total of386 above 14 years old hospital admitted patients undergoing elective surgery in different departments of Patan Hospital were included. Data was collected during the pre-anesthetic evaluation one day before surgery. Perception of patients in relation to educational level and previous exposure to surgery and chi-square test was done at p